Peningkatan Pemahaman Digital Supply Chain dalam Mendukung Visibilitas dan Kinerja Operasional melalui Kegiatan Penyuluhan Bagi Akademisi dan Praktisi Industri - Okin Ringan Purba; Sonya Sidjabat; Muhammad Riza Affiat; Muhamad Ashari Syafril; Rehani Fitrina (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The development of digital technology in the Industry 4.0 era has significantly influenced supply chain systems in the industrial sector. Digital Supply Chain is the integration of digital technologies such as Internet of Things (IoT), Big Data Analytics, Cloud Computing, and RFID to improve visibility, efficiency, and operational performance of companies. However, the limited understanding of academics and industry practitioners regarding the implementation of digital supply chain remains a challenge in facing digital transformation. Therefore, counseling activities were conducted to enhance participants’ understanding of the importance of supply chain digitalization. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation during the counseling activities. The results showed that the counseling activities successfully improved participants’ understanding of digital supply chain concepts, the benefits of digital technology, and its impact on supply chain visibility and operational performance. Participants understood that the implementation of Digital Supply Chain can improve operational efficiency, accelerate distribution processes, reduce logistics costs, and support real-time decision-making. In addition, participants also understood implementation challenges such as technology investment costs and the need to improve human resource competencies. This activity demonstrates that counseling serves as an effective educational approach in improving the readiness of academics and industry practitioners to face digital transformation in the Industry 4.0 era.